Clinical Cell Therapy Guidelines for Neurorestoration (IANR/CANR 2017). Issue 2 (February 2018) - Huang, Hongyun; Young, Wise; Chen, Lin; Feng, Shiqing; Zoubi, Ziad M. Al; Sharma, Hari Shanker; Saberi, Hooshang; Moviglia, Gustavo A.; He, Xijing; Muresanu, Dafin F.; Sharma, Alok; Otom, Ali; et al.
Cell therapy has been shown to be a key clinical therapeutic option for central nervous system diseases or damage. Standardization of clinical cell therapy procedures is an important task for professional associations devoted to cell therapy. The Chinese Branch of the International Association of Neurorestoratology (IANR) completed the first set of guidelines governing the clinical application of neurorestoration in 2011. The IANR and the Chinese Association of Neurorestoratology (CANR) collaborated to propose the current version "Clinical Cell Therapy Guidelines for Neurorestoration (IANR/CANR 2017)". The IANR council board members and CANR committee members approved this proposal on September 1, 2016, and recommend it to clinical practitioners of cellular therapy. These guidelines include items of cell type nomenclature, cell quality control, minimal suggested cell doses, patient-informed consent, indications for undergoing cell therapy, contraindications for undergoing cell therapy, documentation of procedure and therapy, safety evaluation, efficacy evaluation, policy of repeated treatments, do not charge patients for unproven therapies, basic principles of cell therapy, and publishing responsibility.